2013
DOI: 10.1371/journal.pone.0062176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Transcriptional Differences between Indigenous and Invasive Whiteflies Reveals Possible Mechanisms of Whitefly Invasion

Abstract: BackgroundThe whitefly Bemisa tabaci is a species complex of more than 31 cryptic species which include some of the most destructive invasive pests of crops worldwide. Among them, Middle East-Asia Minor 1 (MEAM1) and Mediterranean have invaded many countries and displaced the native whitefly species. The successful invasion of the two species is largely due to their wide range of host plants, high resistance to insecticides and remarkable tolerance to environmental stresses. However, the molecular differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Wang et al . 17 further showed that invasive whiteflies could perform better than indigenous whiteflies on tobacco due to their high activity of detoxification. However, these studies only reported the short-term response of whitefly to unsuitable host plants.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . 17 further showed that invasive whiteflies could perform better than indigenous whiteflies on tobacco due to their high activity of detoxification. However, these studies only reported the short-term response of whitefly to unsuitable host plants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, next generation sequencing technologies have revolutionized the fields of genomics and transcriptomics, providing an opportunity for the rapid and cost-effective generation of genome-scale data [ 25 ]. These technologies have been applied successfully in many invasive species, including Bemisia tabaci [ 26 , 27 ], Anguillicola crassus [ 28 ], Aedes aegypti [ 29 ] and Mytilus galloprovincialis [ 30 ]. In the present study, we sequenced and assembled the transcriptome of the native C. cahayensis from mainland China and the invasive P. canaliculata using de novo sequence assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Plants were cultivated with a potting mix (a mixture of peat moss, vermiculite, organic fertilizer, perlite in a 10 : 10 : 10 : 1 ratio by volume) in plastic pots and grown in whitefly‐proof glasshouses at 27 ± 1 °C, 14 : 10 h L : D, and 40%−60% relative humidity (RH). All the plants used for experiments were grown to the 5−6 fully expanded true leaf stage and all insects used in various treatments were placed onto the lower surface of the third to fifth leaves counted from the top of the plant (Wang et al ., ).…”
Section: Methodsmentioning
confidence: 97%